Gingival Health Status in Children with and without Cleft Lip and Palate: A Case Control Study - Kausalyah Krisna Malay1 , Vignesh Ravindran2, Jayanth Kumar3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cleft lip and palate were classified as followed by Veau in 1931. The major four groups are clefts of softpalate, clefts of hard palate, unilateral clefts of the lip, alveolus and palate, bilateral clefts of the lip, alveolusand palate. Gingival health in children is one of the important factors to be taken into a serious problem as itmay progress to jeopardize the periodontium of the adult. It affects the periodontal disease in the inceptionof earlier in life. In dentistry, it is important for a dentist to recognize early and diagnose gingival diseasesto optimize treatment outcome. To determine the gingival health status in children with and without cleftlip and palate. The purpose of the study was to analyse the gingival status in children with and without cleftlip and palate (a case control study). A study was carried out by collecting data by reviewing patients dataand analysing the data of 86000 patients between June 2019 and March 2020 at the private dental institute.The sample size that was taken included 6 children with cleft lip and palate (case group) and 6 childrenwithout cleft lip and palate (control group), who came to the private dental institute for consultation. Thegingival health status was evaluated using OHIS score and was compared between the groups. Data wasstatistically analysed using SPSS 2.0, Mann-Whitney U Test was conducted. Result was recorded. Thechildren with cleft lip and palate showed similar OHI-S scores compared to children without cleft lip andpalate. Therefore, it was concluded that within the limitations in current study, there was no difference inoral health status between children with cleft lip and palate and children without cleft lip and palate.